A molecular dynamics study of water-soluble polymers: analysis of force fields from atomistic simulations. Issue 4 (24th March 2019) - Rukmani, Shalini J.; Kupgan, Grit; Anstine, Dylan M.; Colina, Coray M.
ABSTRACT: A force field (FF) analysis was performed on three water-soluble polymers (PAM, PNIPAAm, and PEO), that are of significant interest for biomedical applications, by measuring the polymer radius of gyration ( Rg ), solvent accessible surface area (SASA), radial distribution functions ( g ( r )), and relative shape anisotropy ( κ 2 ) in dilute conditions. Three generalised FFs were utilised to model PAM and PNIPAAm (DREIDING, GAFF, and GAFF2) in conjunction with five water models: SPC, SPC/E, TIP3P, TIP4P, and TIP4P/2005. It was found that the DREIDING FF showed better agreement with PAM experimental data reported for Rg, irrespective of the water model. For PNIPAAm, the DREIDING FF was also the best performing among the FFs studied; however, the choice of water model played an important role in the predicted properties. The trends in SASA and κ 2 are consistent with Rg . For PEO modelled with the CHARMM C35r FF, all water models except TIP3P resulted in good agreement with experimental and previous simulation data. These results highlight the considerable impact that polymer and water FFs can have on sampling appropriate polymer conformations in solvated systems.